WEAVING PATHS TOWARDS THE INCLUSION OF STUDENTS WITH AUTISTIC SPECTRUM DISORDER - Fernanda Wunder da Silva, Karla (Revista Gênero e Interdisciplinaridade, 2024)
This text aims to reflect on the first moments of inclusion in regular education of students who have a diagnosis of Autism Spectrum Disorder, listing some possible alternatives for the moment, taking into account the characteristics inherent to the disorder, also mentioning the feelings initials of teachers, colleagues, family members and the feelings experienced by the student himself. It points out that inclusion can happen when those involved are open and available for new learning, for building new knowledge and new ways of teaching. It also points out suggestions, possible trajectories, providing reflection on teaching practice in an inclusive environment, highlighting the importance of the teacher’s role in the success of inclusion when in partnership with the family and with a view that goes beyond the pathology, which thinks about the subject’s potential and learning possibilities.